The Healing Analysis of II Degree Burn from Surgery Essential Oil Ointment (Curcuma Longa) in Wistar Rats (Rattus Norvegicus) - Chen Wei; Florenly Florenly; Dewi Riastawaty Purba; Fioni Fioni (Budapest International Research and Critics University, 2022)
Data in Indonesia the death rate from burns is still high at around 40%, mainly caused by severe burns. The most potential medicinal turmeric plant is its rhizome, which contains the phenolic compound curcumin and essential oils. Some of the benefits of turmeric antioxidants, anti-inflammatory, anti-cancer, acetylcholinesterase activity inhibitors, anti-fungal, and anti-bacterial. This study aims to find out the phytochemical content and effects of Turmeric Essential Oil Ointment (Curcuma longa Linn) in curing grade II burns in Wistar rats (Rattus norvegicus). This type of research is experimental with a pre-post approach and post-test control group design. The study was conducted at Riwandi Pet Shop and Animal House March-May 2021. The research sample is turmeric (Curcuma longa) obtained from a traditional market in the city of Medan and identified in herbarium Medanese (MEDA), Laboratoirum Taxonomy of Plants, Department of Biology, Faculty of Mathematics and Natural Sciences (FMIPA), University of North Sumatra, Medan. The test animal is a Wistar strain rat with as many as 20 tails divided into 4 treatment groups, so each group consists of 5 rats. The results of the study contained significant differences in the epithelial period of the standard group, 10% turmeric ointment and 15% against the control group. However, in the turmeric ointment group and the standard group, there was no difference in epithelialization periods. This is evident from the value P < 0.05 (Value P = 0.029). The healing effects of burns possessed by Turmeric ointment are both 10% and 15% and nebacetin ointment as standard shows significant differences. Where the wound contraction rate of turmeric ointment is 15% better than nebacetin ointment as standard. But in both turmeric ointments, both 10% and 15% and nebacetin ointment as standard did not show significant differences in the parameters of the epithelial period.